Implementasi Teams Games Tournament Berbasis Quizizz pada Proses Pembelajaran Dasar-Dasar Teknik Ketenagalistrikan: Analisis Efektivitas - Cahyono, Andi Petta Wahyu; Yanto, Doni Tri Putra (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2025)
This study aims to test the effectiveness of the implementation of the Teams Games Tournament cooperative learning model based on Quizizz in the Basics of Electrical Engineering subjects for class X Electrical Engineering students at SMK Negeri 1 Lembah Melintang. The implementation of this model aims to enhance student active participation and learning outcomes in the course. This study used a quasi-experimental method with a pretest-posttest control group design. This study involved 63 class X Electrical Engineering students registered in the 2024/2025 academic year. To measure its effectiveness, students were divided into experimental and control groups, and both groups were given a pretest before learning and a posttest after learning. The pretest and posttest scores were then analyzed using the N-Gain Score and Effect Size calculations. The results showed that the N-Gain Score of the experimental group was in the medium category, while the control group only reached the low category. Additionally, the Effect Size calculation yielded a high category. Thus, it can be concluded that the implementation of the Quizizz-based Teams Games Tournament type cooperative learning model is effective in increasing active participation and student learning outcomes in the Basics of Electrical Engineering subjects.